Sistem Komposter Otomatis Pengolahan Limbah Organik di Laboratorium Kewirausahaan Manajemen Agroindustri PSDKU Sidoarjo - Devi, Susan; Syaifulloh, Achmad; D.R, Ika Puspitasari; M., Wahyu Tri; Munshif, Zayd Al (Jurnal Pengelolaan Laboratorium, 2025)
Organic waste is a type of trash that practical operations in the Agro-Industrial Management Entrepreneurship Laboratory at PSDKU Sidoarjo produce but have yet to deal with explicitly. A method to manage organic waste from practical activities is to employ it as organic fertiliser. At PSDKU Sidoarjo, organic fertiliser manufacture is often conducted solely during practical sessions via a composter. Technicians manually assembled the laboratory-scale composters to meet the requirements of the actual job. The challenges encountered with the manual composter include the fact that the quantity of EM4/Bioactivator applied meets expectations, but the manual mixing performed by students resulted in inconsistent mixing outcomes. This research aims to transform the current manual composter in the entrepreneurship laboratory into an automatic composter capable of processing organic waste from the laboratory while establishing a spraying timer that accurately produces the requisite quantity of bioactivator (EM4) according to the research specifications. The study was conducted in the Agroindustry Management Entrepreneurship Laboratory at PSDKU Sidoarjo from May to November 2024,  financed by the PNBP of Jember State Polytechnic 2024. This study has three phases: designing an aerobic organic composter with an automated mixer and sprayer system, building the automated composter, and implementing organic waste management. The study effectively created an automated composter that disperses 125 ml of EM4 liquid for 58 seconds for every 1 kilogram of organic waste.